PERAN POLA ASUH ORANG TUA DALAM MEMBANGUN KETERAMPILAN BERPIKIR KRITIS PADA ANAK - Fadhil, Delani Farras; Barokah, Umi Zaroh; Faizah, Yusrin Nur (FASHLUNA, 2024)
Critical thinking is a skill that must be formed from an early age, where children will process and then create a structured series of thoughts from information that they can understand. The most influential indicator of critical thinking skills is the parenting pattern applied by parents, where children are shaped by parents through the policies they choose and the culture they implement from an early age. This research aims to explain the role of parenting patterns in the development of children's critical thinking skills. The method used in this research is the literature study method (library). This research shows that democratic parenting is a parenting pattern that is capable and appropriate in helping to develop critical thinking skills optimally. This is because parents create a free and enjoyable atmosphere for children, not being restrained or too liberated, children are accustomed to having opinions and taking part in solving problems, where and this will indirectly shape children's independence, discipline and responsibility. This indicator plays the most role in forming children's critical thinking skills.